Transformative Experience of Reading Digital Literature in Social Media - Syahria, Nukmatus; Setiawan, Rahmat; Andanty, Ferra Dian; Iasya, Lubna; Adhim, Syarif (The Study Program of English Education of Palangka Raya University, 2025)
Social media is inevitable part of culture and as the consequence, reading behaviour transforms. This study investigates how digital literature in social media is leveraged through Instagram Reels and TikTok videos, transforming the reading experience in English language acquisition. Employing a phenomenological qualitative methodology, data were gathered via in-depth interviews with three fourth-semester students who participated in the Digital Literature course. The thematic analysis of the data uncovers three primary findings: first, digital literature is favoured for its concise and familiar format that aligns with everyday experiences; second, the interpretation of texts is facilitated by themes and language styles that closely mirror the emotional realities of students; third, digital platforms create opportunities for self-expression, allowing students to experience freedom in writing, sharing, and reflecting on their own personal experiences. The findings of this study highlight that digital literature transcends being merely an alternative medium in literacy education; it embodies a humanistic practice that intertwines language, emotions, and existence. The findings suggest a need to rethink English teaching methods to be more flexible, inclusive, and focused on the emotional experiences of students.